Clinical Symptoms, Endoscopic Imaging and Stroboscopic Imaging in Patients with Vocal Fold Polyp at National ENT Hospital from August 2020 to May 2021 - Manh Duc, Phung; Dinh Thi, Dao; Tuan Son, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4DO - 10.25073/2588-1132/vnumps.4336, 2021)
Vocal fold polyps are one of the most frequent benign laryngeal lesions, impacting the quality of voice of patients. This study aims to describe clinical characteristics, endoscopic and stroboscopic imaging in patients with vocal fold. The study used clinical images and histopathology to describe case series of 32 patients diagnosed with vocal fold polyps from august 2020 to May 2021. The study results show that the average age of the subjects was 42.1 ± 12.3; the most common risk factor was laryngopharyngeal reflux (71.8%); the most common symptoms were hoarseness (100%), of which moderate hoarseness was 59.4%), sore throat - 50%, vocal fatigue - 43.7%; total vhi-30 score was mostly at mild significant affect (71.9%); polyps were usually found in the mid-third of the free margin (65.6%) and vocal fold incompletely closed (100%). The results of stroboscopy show that the presence of mucosal waves was 96.9% and wave amplitude decreased by 68.8%. Taken together, hoarseness is the main symptom and the reason why patients seek medical attention and the position of the vocal fold polyps is usually in the mid-third of the free margin, affecting the anatomy and voice function of the vocal folds. Keywords Vocal fold polyp, clinical characteristics, endoscopic imaging, stroboscopic imaging, LPR. References 1] N. K. Hoa, T. C. Hoa, Benign Vocal Cord Lesions, Review of 315 Cases of Surgery at the Laryngeal Surgery Department - National Hospital of Otolaryngology, Journal of Practical Medicine, 2006, pp. 2-6 (in Vietnamese). [2] A. Zhukhovitskaya, D. Battaglia, S. M. Khosla et al., Gender and Age in Benign Vocal Fold Lesions, the Laryngoscope, 2014, pp. 193. [3] N. N. Lien, P. T. Canh, The Basic Ear Nose Throat, Medical Publishing, Hanoi, 1997. [4] N. P. Mai, Clinical Features and Treatment outcomes Benign Laryngeal Tumors at the ENT Center in Ho Chi Minh City, Thesis of a Specialist Doctor 2, Ho Chi Minh Medical University, 1999, 55-67 (in Vietnamese). [5] F. A. Sakaé et al., Vocal Fold Polyps and Cover Minimum Structural Alterations, Associated Injuries, Otorinolaryngol, Vol. 70, 2004, pp. 1-6. [6] N. A. Kawase, H. Hirose et al., A Statistical Study of Vocal Cord Nodule, Vocal Cord Polyp and Polypoid Vocal Cord, with Special Reference to the Physical and Social Histories of Patients, Ann Bull RilpHo, Vol. 16, 1982, pp. 235-245. [7] M. V. Akdogan , O. Topal, S. S. Erbek, Expression of a Disintegrin and Metalloproteinase -33 Protein in Vocal Fold Polyps, J Laryngol Otol, 2015, pp. 688-692. [8] T. X. Hai, Clinical Features Pathology of Vocal Cort Polysand Affect of Voice Quality, Thesis of a Specialist Doctor 2, Hanoi Medical University, Vol. 18, 2006, pp. 76-77 (in Vietnamese). [9] Y. Zhang, Chaotic vibrations of a Vocal Fold Model with a Unilateral Polyp, J Acoust Soc Am, 2004, pp. 115. [10] N. Q. Hung, Clinical Features Pathology, of Vocal cort Cys and Affect of Voice Quality, Thesis of Master, Hanoi Medical University, Vol, 21-13, 2006, pp. 59 - 70 (in Vietnamese) [11] C. A. Cielo, L. S. Finger, J. C. Rosa, A. R. Brancalioni, Organic and functional Lesions: Nodules, Polyps and Reinke’s Edema, Rev CEFAC, 2011, pp. 735-748. [12] A. Yamauchi, H. Imagawa et al., Quantification of Vocal Fold Vibration in Various Laryngeal Disorders Using High-Speed Digital Imaging, J Voice, Vol. 30, 2016, pp. 205-214.